Implikasi Mediasi Bagi Para Pihak yang Berperkara di Pengadilan Agama Malang - Rahmawati, Erik Sabti (De Jure: Jurnal Hukum dan Syari'ah, 2016)
The decline in family endurance in dealing with conflict, leading to increased divorce rate in Indonesia. Various attempts have been made to reduce the number of divorce, such as integrating mediation in the settlement process of the court. Nevertheless, the implementation of mediation has not been able to meet the expected target. This article aims to understand the procedure and the process of mediation conducted in the Religious Court of Malang Regency. Then, it describes the experiences and expectations of litigants. The study states that the implementation of mediation in the Religious Court of Malang regency has been conducted in accordance with the mechanism regulated by the the Regulation of the Supreme Court (PERMA) 1 in 2008, although in some instances has not run as precisely such provisions. Implementation of mediation in the Religious Court of Malang Regency provide benefits to the parties, although not much to revoke the lawsuit after mediation. But the parties then clearly understand the problems they face, avoiding revenge, divorce peacefully, and the parties feel more prepared for next trial.Menurunnya ketahanan keluarga menghadapi konflik menyebabkan meningkatnya angka perceraian di Indonesia. Berbagai upaya telah dilakukan untuk menekan angka perceraian, salah satunya mengintegrasikan mediasi dalam proses penyelesaian perkara di pengadilan. Meskipun demikian, pelaksanaan mediasi belum mampu memenuhi target yang diharapkan. Artikel ini bertujuan memahami prosedur dan proses mediasi yang dilakukan di Pengadilan Agama Kabupaten Malang. Kemudian mendeskripsikan pengalaman dan harapan para pihak yang berperkara agar mediasi. Pelaksanaan mediasi di Pengadilan Agama Kabupaten Malang telah dilakukan sesuai dengan mekanisme yang telah diatur dalam Peraturan Mahkamah Agung (PERMA) No.1 Tahun 2008, meskipun dalam beberapa hal belum berjalan sesuai ketentuan.Pelaksanaan mediasi di Pengadilan Agama Kabupaten Malang memberikan manfaat bagi para pihak meskipun tidak banyak yang kemudian mencabut gugatan. Misalnya, memahami dengan jelas permasalahan yang mereka hadapi, tidak ada dendam, bercerai dengan damai, dan para pihak merasa lebih siap untuk menghadapi sidang selanjutnya.